Spatial selection of features within perceived and remembered objects - Astle, Duncan E.; Scerif, Gaia; Kuo, Bo-Cheung; Nobre, Anna C. (Frontiers in Human Neuroscience, 2009)
Our representation of the visual world can be modulated by spatially specific attentional biases that depend flexibly on task goals. We compared searching for task-relevant features in perceived versus remembered objects. When searching perceptual input, selected task-relevant and suppressed task-irrelevant features elicited contrasting spatiotopic ERP effects, despite them being perceptually identical. This was also true when participants searched a memory array, suggesting that memory had retained the spatial organisation of the original perceptual input and that this representation could be modulated in a spatially specific fashion. However, task-relevant selection and task-irrelevant suppression effects were of the opposite polarity when searching remembered compared to perceived objects. We suggest that this surprising result stems from the nature of feature- and object-based representations when stored in visual short-term memory. When stored, features are integrated into objects, meaning that the spatially specific selection mechanisms must operate upon objects rather than specific feature-level representations.